Projeto político de formação do enfermeiro: contextos, textos, (re)construções - Miranda, Moemia Gomes de Oliveira (2010)
This research analyses politic Project for nursing education, in its articulation with economical, political and social context of 1970s and 1980s in national level and, in special, nurse formation process in FAEN/UERN space, situating it on the context of Brazilian sanitary reformation movement and participation movement. The thesis is firmed on the sense of explaining whether that movement circa the nurse formation process has been able to build necessary instruments for the transformation of biomedical formation model historically consolidated, in the perspective of conceiving another model anchored on social determination of health/illness process, with the purpose of assuring ethical and political commitment with the SUS praised by sanitary reformation. The study visualized the object considering its specificity, its concrete historical determinations and institutional as well as organizational relationships that permeate possibilities of valorizing it, analyzing it, interpreting it and rebuilding it. Its operationalization occurred in three movements, it means, bibliographical review; documents study; interviews and focal groups realized with professors of the institution. We can apprehend as main results that the nurse formation process has incorporated widely spread conceptions by the sanitary reformation movement and participation movement, assuming the commitment with transformation of health services and social reality. Nevertheless it prevails, still, amongst some professors in the same institutional space, the commitment to a predominantly technicist formation, focused on instrumental knowledge. Opinion divergence explicit diversity of conceptions circa education and, as consequence, distinct political commitments, also contradictory to formation. Thus, there is a lacuna between what is foreseen on political pedagogical project and what is rendered in FAEN/UERN, evidencing the clash related to conceptual bases of formation project. Interpretations, divergent political attitudes and resistances to the process allowed several formation ways. However, formation under new conceptual bases, find limits on the context of social politics implemented in Brazil during the 1990s, neoliberal-based, expressed on expansion and consolidation of health private system, managed by market rules, strengthening biomedical formation model. Notwithstanding, there is a favorable to its implementation, starting from the first years of 21st century, moment when Brazilian sanitary reformation reappear on health speech, as well as facing the policy of permanent education in health. This reality explicit a process of dialectical tension between instituted and institutor, anticipating the moment of scission or adaptation and return to what is already known. Despite of clashed, knowledge, accumulated experience, contribution to services, the construction of partnerships out of university space and articulation with national movement of (re)orientation of nurse formation, have been constituted as vital instruments to offer support to formation in FAEN/UERN. Still, we consider necessary the (re)visitation to FAEN/UERN politic pedagogical Project considering the existing and implemented construction, without, yet, depreciate the norther axis of the project at the reaching of its intentionality